Self-Selection, Immigrant Public Finance Performance and Canadian Citizenship - Don J. DeVoretz; Sergiy Pivnenko (Institute for the Study of Labor (IZA), 2005)
This paper consists of two parts focusing on the immigrant?s decision to acquire Canadian citizenship, and her subsequent performance as a taxpayer and recipient of public finance transfers. Our results support the view that selectivity bias appears in Canadian immigrant citizenship decisions and varies by immigrant gender and source country groups. Our Oaxaca decomposition results demonstrated the importance of the human capital endowment in explaining selectivity corrected citizenship -non-citizenship earnings differences. Next, we confirmed the standard results that the naturalization decision is conditioned by the expected wage gain , level of education, marital status, age and presence of children. At the macro level, our study focused on the implications of Canadian citizenship for the lifetime public finance contributions by naturalized immigrants. All immigrants, regardless of their source country group and citizenship status, made a positive contribution to Canada?s treasury circa 1996 over their life cycle. Naturalized citizens from OECD countries contributed the largest public finance transfers exceeding the corresponding value for the Canadian -born by more than 14,000. In addition, naturalized citizens made higher net contributions than their non-citizen counterparts regardless of source country. The relatively poor public finance performance of non -citizens was explained by their lifetime low income and low tax payments.
Keywords: F22; J68; J61; 330; citizenship; immigration; public finance; Canada; Staatsangehörigkeit; Migranten; Lebenseinkommen; Steuer; Sozialtransfer; Schätzung; Kanada